Protocol for high-throughput electron tomography exemplified on centrioles in primary human plasma cells - Sebastian Köhrer; Tobias Dittrich; Martin Schorb; Isabella Haberbosch; Yannick Schwab; Alwin Krämer (STAR Protocols, 2023)
Summary: Electron microscopy is the gold standard to characterize cellular ultrastructure. However, production of significant morphometrical data is highly limited by acquisition time. Here, we describe a semi-automated high-throughput strategy using single-axis serial section electron tomography to investigate and analyze centriole ultrastructure in bone-marrow-derived, primary human CD138pos plasma cells. The protocol comprises steps for electron microscopy sample preparation, semi-automated transmission electron microscopy screening, and screening evaluation for cells of interest. Thereafter, we detail tomography acquisition, data reconstruction, and joining.For complete details on the use and execution of this protocol, please refer to Dittrich et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.